Pengaruh Kepemimpinan terhadap Kinerja Pegawai di Kantor Camat Gandus kota Palembang - Yuliana Yuliana (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
This study aims to examine the influence of leadership on employee performance at the Gandus sub-district office in Palembang. This research design uses field research with a quantitative approach with a total sample of 40 employees at the Gandus Sub-District Office, Palembang City. The statistical test of the hypothesis uses Simple Linear Regression analysis with the help of the SPSS 22 statistical program. From this research, the results between the leadership variable and the employee performance variable are obtained (r) of 0.493. This means that the two variables have a moderate degree of relationship, or in other words, the leadership variable has an influence of 49.3% on employee performance. While the rest is influenced by other factors outside of this study. The direction of the relationship between the two variables is positive, it means that the better the leadership in an organization, the better the employee's performance. While the t value is 6.075 with a significance value of 0.000 <0.05, which means that there is a significant influence between the variable (X) leadership on the variable (Y) employee performance. In conclusion, there is an influence of leadership on employees at the Gandus sub-district office, Palembang City Keywords: Influence, Leadership, Employee Performance, Quantitative